2016
DOI: 10.1016/j.celrep.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mitochondrial Requirements for Radially and Non-radially Migrating Cortical Neurons: Implications for Mitochondrial Disorders

Abstract: Summary Mitochondrial dysfunction has been increasingly linked to neurodevelopmental disorders such as intellectual disability, childhood epilepsy and autism spectrum disorder, conditions also associated with cortical GABAergic interneuron dysfunction. Although interneurons have some of the highest metabolic demands in the postnatal brain, the importance of mitochondria during interneuron development is unknown. We find that interneuron migration from the basal forebrain to the neocortex is highly sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…Others have used the human brain transcriptome to investigate unifying mechanisms of ASD and found that ASD candidate genes were enriched in co-expression modules of mitochondrial function (Mahfouz et al, 2015). But fewer studies have revealed molecular mechanisms for how mitochondria can impact ASD (Ebrahimi-Fakhari et al, 2016; Lin-Hendel et al, 2016; Novarino et al, 2012), which is a daunting task given that mitochondrial disorders and autism both exist on spectrums (Amaral et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Others have used the human brain transcriptome to investigate unifying mechanisms of ASD and found that ASD candidate genes were enriched in co-expression modules of mitochondrial function (Mahfouz et al, 2015). But fewer studies have revealed molecular mechanisms for how mitochondria can impact ASD (Ebrahimi-Fakhari et al, 2016; Lin-Hendel et al, 2016; Novarino et al, 2012), which is a daunting task given that mitochondrial disorders and autism both exist on spectrums (Amaral et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…[80][81][82] Since inhibitory neurons migrate longer distances to reach their final destinations than excitatory neurons, they might be more susceptible to various factors that affect neuronal migration. 83 As mentioned above, Yang et al found a significant negative correlation between the mRNA expression of somatostatin in the gray matter and the densities of NeuN-positive neurons in the WM. This finding suggests the presence of deficits in the migration of the inhibitory neurons from the WM to the gray matter in patients with schizophrenia, which may also explain the inhibitory dysfunction observed in schizophrenia.…”
Section: Migration Failure Of Gabaergic Neuronsmentioning
confidence: 84%
“…Upon leaving their birthplaces, the inhibitory neurons invade the dorsal forebrain and migrate tangentially in the subventricular zone and marginal zone (MZ; the most superficial area of the neocortex and future Layer I) in the neocortex, and then enter the cortical plate (CP; future gray matter), interact with the excitatory neurons, and become distributed among the latter . Since inhibitory neurons migrate longer distances to reach their final destinations than excitatory neurons, they might be more susceptible to various factors that affect neuronal migration …”
Section: What Is the Cause(s) Of The Increased Densities/number Of Wmmentioning
confidence: 99%
“…The function of ANT1 has been examined in the heart and the neuron, both of which strongly express ANT1, but its functions in immune cells remain unclear . In the present study, we examined whether ANT1 regulates inflammatory cytokine expression in the macrophage‐like cell line, RAW 264.7, because cytokine expression plays important roles in immune cells.…”
mentioning
confidence: 99%
“…Apart from the mitochondrial diseases, ANT1 plays roles in various biological processes. For example, Lin-Hendel et al reported that the inhibition of ANT1 disrupts the nonradial migration of interneurons, but not the radial migration of cortical projection neurons [8]. Furthermore, ANT1 overexpression causes apoptosis by recruiting NF-jB to mitochondria [9,10].…”
mentioning
confidence: 99%